Internalizing Al-Islam and Kemuhammadiyahan Values Within Muhammadiyah Student Organizations - Irsyad Kholili Saputra Irsyad; Shabrina Najma Ulya; Rizka Ammalia; Najmi Adzra Syahidah; Silatulqolbi Aulia; Fakhrurazi Fakhrurazi (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
The Al-Islam and Kemuhammadiyahan (AIK) cadre system is one of the strategic instruments in fostering students' character development and organizational capacity within Muhammadiyah Higher Education institutions. AIK functions not only as a compulsory institutional course but also as a means of ideological cadre formation oriented toward strengthening Islamic values, Muhammadiyah principles, and student leadership. This study is motivated by the importance of reinforcing the role of AIK in supporting the sustainability and quality of student organizations grounded in the values of progressive Islam. The purpose of this study is to examine the role of the AIK cadre system in developing student organizations and its implications for strengthening organizational culture. The research method employed is a literature review, involving the analysis of national scholarly journals, academic books, and institutional documents relevant to AIK, cadre formation, and student organizations. The data were analyzed using a descriptive-analytical approach to obtain a comprehensive conceptual understanding. The findings indicate that the AIK cadre system plays a crucial role in shaping students' religious character, leadership ethics, and ideological commitment within organizational activities. The internalization of AIK values encourages the development of responsibility, discipline, solidarity, and social service orientation in student organizational practices. The implications of this study suggest that strengthening the AIK cadre system on a sustainable basis can serve as a foundation for building student organizations that are ethical, competitive, and aligned with the vision and mission of Muhammadiyah in higher education.